External evaluation of the ESAF : report - Botchwey, Kwesi; Collier, Paul; Gunning, Jan; Hamada, Kōichi, 1936- (International Monetary Fund, 1998)
This study concentrates on three topics: 1) social policies and the composition of government spending during ESAF-supported programs; 2) development in countries' external positions during ESAF-supported programs; and 3) the determinants and influence of differing degrees of national ownership of ESAF-supported programs.